KEDUDUKAN ANAK ZINA DITINJAU DARI YURIDIS NORMATIF - Syamsuddin Syamsuddin; Noer Azizah (Fakultas Agama Islam Universitas Nurul Jadid, 2021)
Problems related to children resulting from adultery are still interesting to discuss, namely in terms of how the position of adultery children in the Compilation of Islamic Law in Article 43 paragraph (1) and Article 272 of the Criminal Code. This research is in the form of normative legal research, namely legal research conducted by researching library materials and using an approach. The type of research used is Libray Research. that the adulterous child in Compilation of Islamic Law or Civil Code both cannot be recognized by his genetic father, while in Compilation of Islamic Law he has more empathy so that the child has a kinship relationship with his mother and mother's family, while in the realm of the Civil Code an adulterous child will not have a juridical relationship with his parents , either to the father or to the mother. However, the child can only obtain rights from his mother and his mother's family. Whereas in the realm of the Criminal Code, adulterous children can only earn what they need according to the ability of their biological parents. But besides that, the adulteress child cannot ask and demand more for what he has given.